Structural and Dynamic Characterization of the C313Y Mutation in Myostatin Dimeric Protein, Responsible for the “Double Muscle” Phenotype in Piedmontese Cattle - Bongiorni, Silvia; Valentini, Alessio; Chillemi, Giovanni (Frontiers in Genetics, 2016)
The knowledge of the molecular effects of the C313Y mutation, responsible for the “double muscle” phenotype in Piedmontese cattle, can help understanding the actual mechanism of phenotype determination and paves the route for a better modulation of the positive effects of this economic important phenotype in the beef industry, while minimizing the negative side effects, now inevitably intersected. The structure and dynamic behaviour of the active dimeric form of Myostatin in cattle was analyzed by means of three state-of-the-art Molecular Dynamics simulations, 200-ns long, of wild-type and C313Y mutants. Our results highlight a role for the conserved Arg333 in establishing a network of short and long range interactions between the two monomers in the wild-type protein that is destroyed upon the C313Y mutation even in a single monomer. Furthermore, the native protein shows an asymmetry in residue fluctuation that is absent in the double monomer mutant. Time window analysis on further 200-ns of simulation demonstrates that this is a characteristic behaviour of the protein, likely depended from the long range communications between monomers. The same behaviour, in fact, has already been observed in other mutated dimers. Finally, the mutation does not produce alterations in the secondary structure elements that compose the characteristic TGF-β cystine-knot motif.